High Breakdown Voltage and Low Dynamic ON-Resistance AlGaN/GaN HEMT with Fluorine Ion Implantation in SiN(x) Passivation Layer - Yang, Chao (Nanoscale Res Lett, 2019)
In this study, we proposed and experimentally demonstrated a high breakdown voltage (BV) and low dynamic ON-resistance (R(ON, D)) AlGaN/GaN high electron mobility transistor (HEMT) by implanting fluorine ions in the thick SiN(x) passivation layer between the gate and drain electrodes. Instead of the fluorine ion implantation in the thin AlGaN barrier layer, the peak position and vacancy distributions are far from the two-dimensional electron gas (2DEG) channel in the case of fluorine ion implantation in the thick passivation layer, which effectively suppresses the direct current (DC) static and pulsed dynamic characteristic degradation. The fluorine ions in the passivation layer also extend the depletion region and increase the average electric field (E-field) strength between the gate and drain, leading to an enhanced BV. The BV of the proposed HEMT increases to 803 V from 680 V of the conventional AlGaN/GaN HEMT (Conv. HEMT) with the same dimensional parameters. The measured R(ON, D) of the proposed HEMT is only increased by 23% at a high drain quiescent bias of 100 V, while the R(ON, D) of the HEMT with fluorine ion implantation in the thin AlGaN barrier layer is increased by 98%.